A new species of Phymatolithon Foslie, P. abuqirensis (Hapalidiaceae, Hapalidiales), from Mediterranean Egypt - Kittle, Ronald P.; Richards, Joseph L.; Sauvage, Thomas; Gabriel, Daniela; Schmidt, William E.; Fredericq, Suzanne (Frontiers in Marine Science, 2022)
Phymatolithon Foslie is one of the most studied and ecologically important genera of crustose coralline algae (CCA) due to their dominant abundance in various marine ecosystems worldwide. The taxonomy of the genus is complex and has been revised and updated many times based on morphological and molecular analyses. We report on a crustose coralline algal species collected in June 2011 via snorkeling in the subtidal zone along the beach Abu Qir on the Mediterranean coast of Egypt, as part of a larger macroalgal diversity survey in the region. The species shows significant sequence divergences (3.5%–14.8% in rbcL; 2.9%–11% in psbA) from other closely related Phymatolithon taxa. Morpho-anatomically, this species possesses the characters considered collectively diagnostic of the genus Phymatolithon, namely, thalli non-geniculate epithelial cells and non-photosynthetic and domed-shaped meristematic cells, usually as short with progressive elongation of their perithallial derivatives. Based on molecular and morphological analyses, we determined that these specimens encompass a new, distinct species that we herein name Phymatolithon abuqirensis. Including this new species, the total number of described Phymatolithon species found in the Mediterranean Sea is now six.